Relationship between serum zinc levels and simple febrile seizures: hospital based case control study - Hubaira, .; Wani, Zubir A.; Qadri, Syed Muneeb R. (International Journal of Contemporary Pediatrics, 2017)
Background: Owing to the excessive susceptibility of the immature brain to temperature, febrile seizures remain one of the common neurological conditions of childhood. Although simple febrile seizures do not pose any increased neurological problems in adult life, but the anxiety, hospitalization and prophylaxis for the episode do call for a genuine concern. A correlation between zinc deficiency and febrile seizures has been proposed and a few studies undertaken have shown mixed conclusions. This case control study was undertaken to compare the serum Zinc levels in patients with simple febrile seizures against the controlled patients with short febrile illness without seizures and to find the correlation if any between simple febrile seizures and serum zinc levels. Methods: The hospital based, observational case control study was done in Batra Hospital and Medical research Centre, New Delhi. A total of 200 children aged 6 months to 6 years admitted in the hospital with history of short pyrexia (fever for 2 days or less) and fulfilling our inclusion criteria were enrolled for the study after taking an informed consent from their attendants and classified into 2 groups of 100 each as cases and controls. Patients with history of simple febrile seizures as cases and those with fever without seizures as controls. A detailed history was taken, and complete physical examination was done on the patients and recorded on a precoded and pretested proforma. The data was analysed on SPSS 17. Results: Our results showed a mean of serum zinc levels in cases as 61.53±15.87 mcg/dl which was found to be lower compared to controls as 71.90+18.50 mcg /dl. Further the difference was found to be statistically significant (P<0.05). Conclusions: Low serum zinc levels in the patients of simple febrile seizures in association with other risk factors may enhance the occurrence of seizures triggered by fever. Thus, a possible correlation exists between the mean serum zinc level and simple febrile seizures.